1901 Utah Laws 139, ch. 124, § 60 - (:unkn) unknown (General Publisher, 1901)
To regulate or prevent the storage of gunpowder, tar, pitch, resin, coal oil, benzene, turpentine, nitroglycerine, petroleum, or any of the products thereof, and other combustible or explosive material, and the use of lights in stables, shops and other places, and the building of bonfires.
--
Keywords: GUN POWDER STORAGE